EDUKASI DAN PENDAMPINGAN GIZI PADA IBU ANAK USIA SEKOLAH DI DESA INDRODELIK KECAMATAN BUNGAH - Nur Qomaria; Rahma Fidania Dwik Nuraini; Yasirotul Hikmah; Nur Habibatus Sholihah; Desty Muzarofatus Sholikhah (Ghidza Media Jurnal, 2022)
Nutritional problems in Indonesia are still often encountered, such as malnutrition and poor breakfast habits. This activity aims to improve and increase the knowledge of schoolchildren's mothers and maintain normal nutritional status in schoolchildren in Indrodelik Village, Bungah District, Gresik Regency. This activity uses a combination research method (mixed method research) with primary data obtained directly from respondents through the implementation of baselines (interviews and filling out questionnaires) in Indro Hamlet, Indrodelik Village. Sampling of activities using purposive sampling method which is carried out when taking baseline data and samples taken are included in the inclusion criteria, namely aged 6 to 12 years. The results of this activity are that there is an increase in the level of knowledge before and after counseling and an increase in respondents' understanding regarding the intake consumed must be nutritionally balanced, although the results of the recall analysis are still not stable from day to day. But it has shown an increase and change in the intake of respondents from before counseling to after counseling.